CONSTITUTIONAL RELEVANCE OF THE PRESUMPTION OF INNOCENCE - ARĂDAN, Constantin-Marius (International Journal of Legal and Social Order, 2022)
In this paper we propose to present the place of the presumption of innocence in the Romanian constitutional landscape and to show that it can be delimited by the notoriety of criminal law. In order to achieve our objective, we briefly presented the situations that can contribute to the definition of the presumption of innocence. Even if the presumption of innocence coexists only in the relationship of "collaboration" with the accused or the defendant, it bears nuances specific to human rights, equity, the rule of law and even the legislative policy of the state. In this sense, the specific discussions will start from the provisions of art. 16 para. (1) and (2) of the Constitution in conjunction with those of art. 23 para. (8) and (11) and from the provisions of art. 4 para. (1) of the Code of Criminal Procedure in order to establish the normative content of the "presumption of innocence". From a simple benefit to the complexity of legal protection is only one step because the presumption of innocence constitutes a fundamental human right through its implications on individual freedom, a fact recognized at the level of the Fundamental Law. Finally, deepening the principle of "presumption of innocence" throughout this article, we believe that it will be natural to conclude that this is a principle of constitutional rank.